Address to the 4th World Reindeer Herders Congress - Walaas, Elisabeth (2009)
It is a great honour for me to open the fourth world congress of the association of world reindeer herders here in Guovdageaidnu- Kautokeino- of which we are proud to say that it is indeed one of the most important centres for traditional and modern reindeer husbandry in the world. Allow me, on behalf of foreign minister Støre and the Norwegian government to congratulate you with this important event. I also convey their best wishes for the congress and your work. It is quite impressive to see so many representatives from so many regions and countries gathered together here in Finnmark to participate in the world congress and its extensive cultural and social programme this week before our Eastern holiday. And let me repeat the words: Tradition and modernity. I think these key words are the clue to the success of the work of your organization, WRH.